Inclusive Language and Academic Lexicography: Médicas Who Want to Be Referred to as Médicos - Barrera Linares, Luis Guillermo (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper deals with the contemporary use of the Spanish feminine word médica, in reference to female professionals who practice medicine. Based on a sample of use of médico/médica compiled from Twitter accounts operated by Venezuelan female medical doctors, and compared with some data captured from web pages, cases of self-reference and exoreference are analyzed, to show the relationship between the use of the feminine medica or the preference for the option of the generic masculine médico. The médico / médica binomial was also investigated as a lemma in the Nuevo tesoro lexicográfico de la lengua española (RAE, NTLLE), with the purpose of verifying its evolution from the first edition of the Diccionario de la lengua española to the present. Despite the early incorporation of médica to the dictionary (1899) and the progress of other similar words (e.g., ingeniera, abogada), the results show female reluctance to self-refer or to being referred to as médicas. The most relevant conclusion is that such preference exceeds the possibility of a linguistic explanation and points to different causes related to discursive sexism, the social prestige of masculine professionals, and public appreciation for professional marketing.